Current clinical spectrum of common variable immunodeficiency in Spain: The multicentric nationwide GTEM-SEMI-CVID registry - Cabañero-Navalon, Marta Dafne; Garcia-Bustos, Victor; Nuñez-Beltran, Maria; Císcar Fernández, Pascual; Mateu, Lourdes; Solanich, Xavier; Carrillo-Linares, Juan Luis; Robles-Marhuenda, Ángel; Puchades-Gimeno, Francesc; Pelaez Ballesta, Ana; López-Osle, Nuria; Torralba-Cabeza, Miguel Ángel; et al. (Frontiers in Immunology, 2022)
Common variable immunodeficiency (CVID) constitutes a heterogenic group of primary immunodeficiency disorders with a wide-ranging clinical spectrum. CVID-associated non-infectious morbidity constitutes a major challenge requiring a full understanding of its pathophysiology and its clinical importance and global variability, especially considering the broad clinical, genetic, and regional heterogeneity of CVID disorders. This work aimed to develop a nationwide, multicenter, retrospective study over a 3-year period describing epidemiological, clinical, laboratory, therapeutic, and prognostic features of 250 CVID patients in Spain. The mean diagnostic delay was around 10 years and most patients initially presented with infectious complications followed by non-infectious immune disorders. However, infectious diseases were not the main cause of morbimortality. Non-infectious lung disease was extraordinarily frequent in our registry affecting approximately 60% of the patients. More than one-third of the patients in our cohort showed lymphadenopathies and splenomegaly in their follow-up, and more than 33% presented immune cytopenias, especially Evans’ syndrome. Gastrointestinal disease was observed in more than 40% of the patients. Among biopsied organs in our cohort, benign lymphoproliferation was the principal histopathological alteration. Reaching 15.26%, the global prevalence of cancer in our registry was one of the highest reported to date, with non-Hodgkin B lymphoma being the most frequent. These data emphasize the importance of basic and translational research delving into the pathophysiological pathways involved in immune dysregulation and diffuse lymphocytic infiltration. This would reveal new tailored strategies to reduce immune complications, and the associated healthcare burden, and ensure a better quality of life for CVID patients.